Proposal of Marketing Strategy for Instalasi RIK Parahyangan Pavilion RSUP Hasan Sadikin Bandung - Nurina, Azniar; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2012)
Along with the changes of social society and the flow of information, customer’s need for quality of service is higher, including health service in hospital. For some people, they perceived health service in private hospital is superior than government-owned hospital. Moreover, some of them preferred to use health service abroad. Since medium – higher economic class customer have ability to choose health service they needed, it is important to inquiry factors that influenced their decision making.The research for this thesis was conducted at RIK Parahyangan Pavilion Hasan Sadikin Hospital in Bandung. The problem is low Bed Occupancy Rate (BOR). Eventhough every year, hospital improve their facility, either added their bed capacity or added supporting facilities, the efforts still did not urge standar usage capacity BOR which is about 85% of occupancy.The main focus of this thesis is to investigate the preference inpatient service of potential customer. This study includes internal and external analysis to determine the dominant criterion in influencing customer preferences to choose inpatient service of particular hospital.The data that had been processed comes from interview and questionnaire. The result are the level of importance, customer perception and position of RIK Parahyangan Pavilion Hasan Sadikin Hospital compared with its competitor. Based on the data and analysis, we can conclude that low awareness of Instalasi Rawat Inap Khusus Parahyangan Pavilion RSUP Dr. Hasan Sadikin Bandung, negative perception of health service and cannibalism became the dominant factor that cause low level in BOR.As solution RIK Parahyangan Pavilion Hasan Sadikin Hospital is to encourage to apply internal marketing communication and below the line marketing to build customer awareness and create positive attitude toward government-owned hospital especially Hasan Sadikin Hospital. Keyword : Awareness, Internal marketing, Below-the-line Marketing